UNITING TRI DHARMA OF HIGHER EDUCATION1 Reflection and Projection of PTAI (IHE) - Wahid, Marzuki (Universitas Islam Negeri Alauddin Makassar, 2014)
Separating among the theory, practice, and 2social transformation in the context of science and movement is extremely dangerous and will only create significant imbalances. In the Islamic context, this separation is clearly contrary to the mission of Islam. Islam always links among faith, science, charity, and welfare in the creation of human life that is fair and humane. In other words, Islam links among the ideological belief, theory, practice, and social foundation, it is expected to further develop IHE to become religious and scientific laboratory by borrowing the term from Prof. Harun Nasution—as a creator of”modern mujtahid.” In the context of campus politic, the students can join the lecturers in a row of politicial interest, but it does not occur in rank of academic, research, and community empowerment. It is ironic, isn’t it! Further impact of the ”crisis” of this academic community, IHE does not have proudly intelectualism icon, whether in the aspects of thought or movement. The scientific nuances of PTAI are nearly alike, there is no academic character that stands out as its strength (uniqueness). ... a fact that we should admit that the academic climate and tradition at the IHE is still fragile, or we can infer that there is still unclear developed fundamental roots and science vision. The lecturers’ expertise cannot also academically be proven by the scientific work and authoritative thinking. The fragile academic tradition and vague science vision are called the